Nondestructive adult age at death estimation: Visualizing cementum annulations in a known age historical human assemblage using synchrotron X‐ray microtomography. Issue 1 (15th November 2018) - Le Cabec, Adeline; Tang, Nancy K.; Ruano Rubio, Valentin; Hillson, Simon
Abstract: Objectives: Adult age at death estimation continues to challenge physical anthropologists. One estimation method involves counting tooth cementum annulations (TCA). Non‐destructively accessing TCA is a critical step to approaching fossil teeth of unknown age and to verifying life history profiles of human ancestors. This pilot study aims to (a) non‐destructively image TCA in teeth from a known age archeological human population by propagation phase contrast X‐ray synchrotron μCT (PPC‐SR‐μCT) (b) test the correlation between real and estimated ages, and the accuracy, precision and bias of age estimates. Materials and Methods: We examine 20 permanent human canines (aged 20–81 years), from a 18th to 19th century known age collection from St. Luke's Church (London, England). We scanned transverse segments of acellular cementum in the apical portion of the middle root third using PPC‐SR‐μCT. We generated virtual transverse sections on which two observers perform two sessions of blind TCA counts. We calculate the estimated ages at death by adding 10 years to the TCA counts. Results: A moderately strong positive linear relationship exists between real and estimated ages ( r = 0.76, p < .001), with an average inaccuracy of 16.1 years and an average bias towards underestimation of 15.7 years. This difference is lower in individuals <50 years (6.8 and 6.5 years, respectively, n = 10) compared with those >50 years (24.9 years, n = 10). Discussion: We reliably imaged and identified TCA in individuals <50 years from a known‐age archeological sample. Scanning refinement will yield a promising alternative to current destructive methods of TCA analyses and to aid access to life history events in adult fossil hominins.